Spectrophotometry Comparison and Microleakage Analysis of Bioactive Glass-Reinforced Resin Infiltrants: An In Vitro Study - Ahmed, Syed Zubairuddin; Alzayer, Sukainah Zaki; Alsaeed, Yasmeen Hassan; Isam, Sakinah Hussain Al (European Journal of General Dentistry, 2025)
White spot lesion management has evolved into minimally invasive approaches, including resin infiltration material and TEETH samples (without any material) used as negative control group.Sixty permanent noncavitated premolars were sectioned into two halves buccolingually (n = 120). Both surfaces artificially produced a white spot lesion and randomly distributed; bioglass (45S5), borosilicate-based bioactive glass (B-BAG), fluoride-based bioactive glass, commercial resin (ICON, as +ve control), and resin without filler (Pure Resin). All the samples were immersed in coffee, soda, orange juice, and artificial saliva for 28 days, and color stability was measured weekly. For penetration depth analysis, the teeth were immersed in 2% methylene blue dye solution for 24 hours at 37°C. The microleakage analysis was performed for all the samples using the stereomicroscope.There were significant differences in the color properties of all the samples for all the groups. Immersion in coffee and soda resulted in significantly increased color alteration compared with orange juice (p = 0.001). The commercial resin-infiltrated group exhibited the highest staining values (p = 0.001). However, following artificial saliva immersion, commercial material has successfully maintained its color properties. After Pure Resin, ICON exhibited the lowest microleakage values while the B-BAG showed the highest microleakage in all the groups.The exposure of specimens to colored solutions resulted in significant color alteration.
Keywords: bioactive glass; color stability; microleakage; resin infiltration; spectrophotometry